DIRECT COSTING–SHOULD IT BE A CONTROVERSIAL ISSUE? - Brummet, R. Lee (The Accounting Review, 1955)
The article focuses on direct costing. It is to find a single subject that can compare during the past few years with direct costing when it comes to popularity for article-writing, speech giving, debates and friendly discussions among people interested in accounting. One is often inclined to think that most everything that can be said for or against direct costing has already been said and that surely the enthusiasm, both pro and con, is soon to give way to newer and perhaps more constructive subject matter for accountants' considerations. Yet there seems still to be considerable uncertainty as to just what the term means and what it implies for accounting purposes. Many of the advantages which are hailed as outgrowths of direct costing procedures have been in use for many years by all informed managements and many of the disadvantages proclaimed by those who find fault with the procedure are aimed at relatively unimportant implications and not at the heart of the matter. At least some of the uncertainty surrounding considerations of direct costing is the result of inappropriate terminology.